Legal Responsibility of Midwives in Handling Deliveries in Karyamulya Village - Muhammad Nur Rohim Rizal Bakri; Zidan Maulana Al Hadi; Mochamad Iqbal Haika; Sanusi; Muhammad Noupel (PT Publikasiku Academic Solution, 2025)
Midwifery services are health services provided by midwives, focusing on women’s health, especially mothers and babies, from pre-pregnancy to postpartum care. Midwives are required to offer services based on responsibility, accountability, and competence, adhering to professional standards and legal regulations. Their authority is regulated by law, allowing them to provide maternal and childcare, reproductive health, and family planning, but medical procedures may only be performed with written delegation from a doctor, except in emergencies or areas lacking doctors. If a midwife commits malpractice or acts outside their authority, resulting in harm, they may be subject to civil, criminal, or administrative sanctions. Patients have the right to seek accountability through legal action for negligence or error, and midwives may also face ethical sanctions under the professional code of ethics. Legal responsibility can extend to doctors and health institutions if delegation of authority is not properly documented or supervised, following the principle of vicarious liability. Disputes arising from midwifery services can be resolved through mediation, arbitration, or the courts; compensation may be required for proven losses.